(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2013)
This work seeks to provide a jurisprudential and normative overview of the treatment of party loyalty in Brazil which, despite being the subject of decisions in writs of mandamus filed with the Federal Supreme Court and of consultations and resolutions of the Superior Electoral Court, is still not a peaceful matter in the doctrine. The complexity of the legal foundations and the intricate changes in the position of the Federal Supreme Court have ended up bringing contours that are not yet clear in the delineation of the issue in Brazilian electoral law. The importance, therefore, lies in simplifying the of the Brazilian party and electoral system with a view to achieving an effective and plural representative democracy.